Analysis of Community Awareness Against Threats to Personal Data Security Through Phishing Websites - M Alvian H Nasution; Joko Dwi Santoso (The IJICS (International Journal of Informatics and Computer Science), 2021)
The threat of personal data security is a very sensitive matter lately, Website Phishing is one of the activities that can trap and threaten someone by deceiving that person. From the results of the Phishing Website, the victim indirectly provides data or information about the victim to the trapper. In this case, Phishing Websites are one of the cyber crimes that are still very often used to retrieve victim data. "What is expected from this research is to obtain a percentage value related to the level of public awareness of the crime of phishing where many people are still unfamiliar with the crime that is increasingly happening through social media, one of which is WhatsApp". Phishing website attacks are carried out by creating a fake website address that is as similar as possible to the original website, then the trapper sends this Phishing website address to the target/victim via Whatsapp social media. In this study, the data collection method will use the quantitative method, which is how to make a questionnaire that will be filled out by 80 respondents who come from the general public who are still unfamiliar with technology. The results of this study will contain the presentation of respondents to the awareness of Phishing Websites, it is hoped that this research will make the general public who are still unfamiliar with Phishing Websites more careful about website threats that can attack at any time.